Profile of thoracic expansion in Congolese school children in Brazzaville: an exploratory study - Moulongo, Jean G. A.; Moussoki, Jean M.; Bopaka, Régis G.; Kambourou, Judicaël; Mouanda Konde, Dorel; Kabengele, Benoît O.; Mabiala Babela, Jean R.; Kayembe Ntumba, Jean M.; Massamba, Alphonse (International Journal of Contemporary Pediatrics, 2026)
Background: To determine the values of chest expansion in Congolese children aged 7 to 12 years, and to investigate the link between chest expansion and anthropometric variables (age, height, BMI), hemodynamic variables (heart rate, blood pressure) and maximum oxygen consumption. Methods: A total of 3745 children (2023 boys and 1722 girls) enrolled in public primary schools in seven districts of Brazzaville were assessed. Anthropometric, hemodynamic and aerobic capacity (VO2max) data were collected; thoracic circumference who has been measured at the axillary and xiphoid levels, was used to assess thoracic expansion. Significance of differences between experimental variables was analysed using a paired t test, Sokal’s to compare thoracic expansion to the axillary and xiphoid levels, between the two sexes, as well as its variations from 7 to 12 years and during the transition from the 7-10 years age group to the 11-12 years age group. Pearson correlation coefficients were used to test the relationship between a few independent variables and thoracic expansion. Results: The mean values of thoracic expansion at the axillary and xiphoid levels were 2.23±0.13 cm (2.45±0.15 cm in boys versus 2.00±0.12 cm in girls; p<0.01) and 2.04±0.11 cm (2.25±0.13 cm in boys versus 1.83±0.10 cm in girls; p<0.01). Chest expansion increased with age, regardless of the level of measurement. Significant differences were found between the 7-10 year and 11-12-year age groups for axillary and xiphoidal chest expansion, regardless of sex. Thoracic expansion was positively correlated with age, height, BMI and absolute VO2max in boys at any measurement level, but only at the axillary level in girls. A negative and close relationship between thoracic expansion determined at the axillary level and heart rate was highlighted. Conclusions: This work revealed age- and sex-related differences in chest expansion, as well as the influence of a few parameters of interest. However, the data obtained deserve verification and validation by larger studies at the national level before possible popularization.